A self-lubricating composite ceramic coating and its preparation process
By introducing modified carbon fibers and composite lubricants into the ceramic coating, a stable lubricating layer is formed, which solves the problems of high friction coefficient and insufficient toughness of the ceramic coating under dry friction conditions, and realizes the self-lubricating performance and wear resistance of the ceramic coating. Sex improvement.
Patent Information
- Application Number
- CN202411231638.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-04
AI Technical Summary
Traditional ceramic coatings have a high friction coefficient under dry friction conditions, and the single component ceramic membrane is insufficient in toughness, which limits its widespread application on the surface of high-speed rotating components.
Modified carbon fiber and composite lubricant are used to improve the bonding strength of carbon fiber and ceramic aggregates through oxidation treatment, and molybdenum disulfide is introduced as a modifier to form a stable lubricating layer, and self-lubricating is prepared by combining sol-gel method and spin coating process. composite ceramic coating.
It significantly reduces the friction coefficient of the ceramic coating, improves its wear resistance and toughness, forms a more stable and long-lasting lubricating layer, and enhances the comprehensive mechanical properties and high-temperature properties of the ceramic coating.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of surface treatment and relates to a self-lubricating composite ceramic coating and a preparation process thereof. Background Art
[0002] In the modern industrial field, the surface properties of metal materials, such as wear resistance and self-lubrication, play a vital role in their overall service life and functional performance. In complex and changing working conditions, especially those involving high friction, heavy load or dry friction conditions, traditional metal materials often face significant wear and energy dissipation problems, which directly weakens the operating reliability of the equipment and shortens its expected service life.
[0003] In order to solve this long-standing technical bottleneck, the field of surface engineering continues to explore and innovate. Among them, ceramic coating technology has become a hot spot for current research and application due to its unique advantages such as good wear resistance, high temperature resistance, excellent corrosion resistance and high stiffness. However, although ceramic coatings have excellent performance in many aspects, they have a relatively high friction coefficient under dry friction conditions, and the toughness of single-component ceramic films is insufficient. These problems have become key factors restricting their widespread application on the surfaces of high-speed rotating parts. Summary of the invention
[0004] The purpose of the present invention is to provide a self-lubricating composite ceramic coating and a preparation process thereof, which has the characteristics of good comprehensive mechanical properties, low friction coefficient, high wear resistance, high temperature resistance, high toughness and self-lubricity.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A self-lubricating composite ceramic coating and a preparation process thereof. The specific process of the preparation process of the self-lubricating composite ceramic coating is as follows:
[0007] S1.1: Use 500 mesh, 800 mesh and 1200 mesh water-abrasive sandpaper to polish the surface of the metal substrate step by step until it is bright, and use deionized water to clean the surface of the substrate;
[0008] S1.2: Place the polished metal substrate in an alkaline cleaning solution for 5 min, wash it with deionized water, and then place it in an acid cleaning solution for 5 min. Wash it with deionized water until the pH of the eluent is 7-8, and dry it at room temperature for 24 h to obtain the metal substrate to be coated;
[0009] S1.3: 85 wt% aluminum isopropoxide was dissolved in a mixture of ethanol and water, heated and stirred at 60 °C for 1 h, hydrochloric acid solution was added to the mixture at a constant drip rate of 1 mL / min using a microinjection pump, and heated and stirred at 60 °C for 1 h to obtain sol A;
[0010] S1.4: Add modified carbon fiber to sol A to prepare a mixed solution B containing 10 mg / L modified carbon fiber, and perform ultrasonic treatment at 60 °C for 30 min;
[0011] S1.5: 3 wt% of the composite lubricant and 1 wt% of the dispersant were added to the mixed solution B, and stirred on a magnetic stirrer at a speed of 500 r / min for 1 h to obtain a gel precursor;
[0012] S1.6: Use a fully automatic spin coater to evenly coat the gel precursor on the surface of the metal substrate to be coated. The spin coating speed is 3000 r / min and the spin coating time is 2 min. Place the metal substrate coated with the gel precursor in a constant temperature drying oven and dry it at 100 °C for 2 h to obtain a dry gel film.
[0013] S1.7: Place the dry gel film in a tubular furnace and calcine it in an argon atmosphere at a temperature of 300-400 °C for 1 h to obtain a coated substrate. After taking it out, use a grinder to polish the surface of the coated film. Then, immerse the coated film in ethanol and let it stand at room temperature for 30 min. After taking it out, dry it naturally to obtain the composite ceramic coating.
[0014] Furthermore, the metal substrate in S1.1 includes stainless steel and alloy.
[0015] Furthermore, the volume ratio of ethanol to water in S1.3 is 1:20-30.
[0016] Furthermore, the concentration of the hydrochloric acid solution in S1.3 is 2 M.
[0017] Furthermore, the preparation method of the modified carbon fiber in S1.4 is as follows:
[0018] S5.1: Soak 50 wt% carbon fiber in acetone for 30 min, wash it several times with deionized water and place it in deionized water, then add concentrated nitric acid solution at a flow rate of 0.5 mL / min, heat and stir at 70 °C for 1 h, and wash it with deionized water to obtain oxidized carbon fiber;
[0019] S5.2: The oxidized carbon fiber is placed in a microwave generator for irradiation, and the modified carbon fiber is obtained after natural cooling.
[0020] Furthermore, the preparation method of the composite lubricant in S1.5 is as follows:
[0021] S6.1: MoS2 was placed in a ball mill for ball milling at a speed of 200 r / min for 1 h. Intermittent ball milling was used with a 1 min break after every 2 min of ball milling to obtain MoS2 powder with a particle size of 500 μm.
[0022] S6.2: Add 5 wt% molybdenum disulfide powder to the polytetrafluoroethylene emulsion and mix them using a high-speed magnetic stirrer at a speed of 1000 r / min for 30 min to obtain a mixture C;
[0023] S6.3: Add 1 wt% titanate coupling agent to mixture C, heat and stir at 60 °C for 1 h to obtain a composite lubricant.
[0024] Furthermore, the dispersant in S1.5 is one of polyethylene glycol and polyvinyl alcohol.
[0025] Furthermore, the setting parameters of the microwave generator in S5.2 are as follows: microwave power is 300 W, irradiation time is 30 min, and irradiation temperature is 200 °C.
[0026] The present invention firstly performs fine treatment on the surface of the metal substrate by gradually grinding with sandpaper and alternately cleaning with alkaline washing solution and acid washing solution, so as to remove impurities such as organic matter and oxides on the surface of the metal substrate, thereby improving the flatness of the surface of the metal substrate, which is beneficial to enhancing the bonding force between the ceramic coating layer and the metal substrate, reducing coating defects, and extending the service life of the coating.
[0027] In order to improve the wear resistance and toughness of the ceramic coating and prevent the ceramic coating from cracking during use, modified carbon fiber materials are introduced into the ceramic aggregate. Nitric acid is used as an oxidant to react with carbon atoms on the surface of the carbon fiber to generate oxygen-containing functional groups such as carboxyl and hydroxyl groups, increase the hydrophilicity and active sites of the carbon fiber surface, increase the adsorption and bonding with the ceramic aggregate, and at the same time, the oxidation treatment can significantly improve the interfacial bonding strength between the carbon fiber and the ceramic aggregate; in addition, the carbon fiber is quickly and evenly heated by microwave irradiation, a non-contact heating method, which further induces physical or chemical changes on the surface of the carbon fiber from the structural level, resulting in surface reconstruction, lattice distortion and other results, improving the heat resistance and aging resistance of the carbon fiber, while increasing the activity and surface energy of the carbon fiber, promoting the interaction between the carbon fiber and the ceramic aggregate, and generating a stable network cross-linked structure with the ceramic aggregate through the sol-gel process, thereby improving the overall performance of the composite material.
[0028] In addition, in order to enhance the self-lubricating properties of the ceramic coating, a composite lubricant is introduced into the gel precursor. Polytetrafluoroethylene has extremely low surface energy and excellent lubrication properties, but pure polytetrafluoroethylene has limitations such as insufficient dimensional stability, large creep and low hardness in high-load applications, which makes it prone to wear. To overcome these shortcomings, molybdenum disulfide is introduced as a modifier. The unique graphite sheet structure of molybdenum disulfide brings it more excellent lubrication properties. This is because the molybdenum disulfide layer is tightly connected by strong covalent bonds, which ensures the stability of the structure, and the layers interact through weak van der Waals forces, which makes it easy for its interlayer structure to slide and peel off relative to each other under the action of external forces, thereby forming a continuous lubricating layer at the friction interface, significantly reducing the friction coefficient. In addition, nano-scale molybdenum disulfide can be more effectively adsorbed on the surface of the wear part due to its large specific surface area and high surface energy, reducing friction and wear, and significantly improving the wear resistance of the ceramic coating. In order to maximize the synergistic effect between molybdenum disulfide and polytetrafluoroethylene, a coupling agent is used as a bridge to strengthen the interfacial bonding between the two. Under high temperature conditions, the active groups in the coupling agent can react chemically with the hydroxyl groups or other functional groups on the surface of molybdenum disulfide to form a stable chemical bond. This chemical bond not only enhances the overall stability of the composite material, but also enables nano-molybdenum disulfide to effectively limit the plastic deformation of the polytetrafluoroethylene molecular chain, thereby improving its hardness and stability.
[0029] The main process of the present invention adopts an environmentally friendly and low-energy gel sol method for film preparation. Aluminum isopropoxide undergoes hydrolysis and polycondensation in an ethanol-water mixed solvent of an appropriate concentration, and hydrochloric acid of an appropriate concentration is added at a constant drip rate to catalyze the hydrolysis reaction of aluminum isopropoxide, inhibit side reactions, and ensure the stability of the sol, and finally form a three-dimensional network structure sol with uniform particle size distribution and good stability. The modified carbon fiber is introduced into the sol, uniformly dispersed by ultrasonic treatment, and then a composite lubricant and a dispersant are added, and a gel precursor is obtained after magnetic stirring. In this process, the carbon fiber enhances mechanical properties and wear resistance, and the lubricant and dispersant optimize the fluidity and stability of the sol, ensuring that the coating is uniform and dense. The fully automatic spin coater coats the gel precursor on a metal substrate, and utilizes the advantages of the spin coating method to achieve uniform coating of large areas and complex-shaped substrates, and regulates the appropriate spin coating speed and time to ensure accurate control of the film thickness. Constant temperature drying removes the solvent, and the precursor solidifies into a film, providing a basis for low-temperature calcination. The coating is calcined in a tubular furnace, and the dry gel film undergoes organic decomposition, phase change and crystallization under the protection of argon gas, and is transformed into a composite ceramic coating. The argon atmosphere can prevent oxidation pollution and ensure the quality of the coating. Finally, grinding and polishing and ethanol immersion further optimize the coating surface and improve its flatness, corrosion resistance and wear resistance.
[0030] Beneficial effects of the present invention:
[0031] (1) By introducing molybdenum disulfide to modify polytetrafluoroethylene and combining it with the chemical action of a coupling agent, a high-performance composite lubricant system was successfully constructed. This system not only inherits the low friction characteristics of polytetrafluoroethylene, but also overcomes its mechanical shortcomings, achieving a more stable, durable and efficient lubricating layer in the ceramic coating, thereby significantly improving the self-lubricating properties and wear resistance of the coating.
[0032] (2) The oxidized functional groups on the surface of the modified carbon fiber help to firmly bond with other components, forming a stable network cross-linked structure, further improving the comprehensive mechanical properties and thermal stability of the composite material. In addition, the present invention adopts a sol-gel method combined with a spin coating method to prepare a ceramic coating, which is easier to carry out than other coating methods, and the reactants can be evenly dispersed at the molecular level during the reaction, preventing the hardness and mechanical strength of the coating material from decreasing due to uneven composition. At the same time, compared with other technologies, the sintering temperature required for the sol-gel reaction is lower, and energy saving and environmental protection are significantly enhanced. DETAILED DESCRIPTION
[0033] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0034]
[0035] The metal substrate used in the examples and comparative examples is made of stainless steel, has a size of Φ30 mm×35 mm, and a thickness of the ceramic coating is 150 μm.
[0036] Example 1
[0037] In this embodiment, the tubular furnace uses a calcination temperature of 300°C.
[0038] S1.1: Use 500 mesh, 800 mesh and 1200 mesh water-abrasive sandpaper to polish the surface of the metal substrate step by step until it is bright, and use deionized water to clean the surface of the substrate;
[0039] S1.2: Place the polished metal substrate in an alkaline cleaning solution for 5 min, the alkaline cleaning solution is a 0.5 M sodium hydroxide solution, wash it with deionized water, and then place it in an acid cleaning solution for 5 min, the acid cleaning solution is a 1 M phosphoric acid solution, wash it with deionized water until the pH of the eluent is 7-8, and dry it at room temperature for 24 h to obtain the metal substrate to be coated;
[0040] S1.3: 85 wt% aluminum isopropoxide was dissolved in a mixture of ethanol and water, wherein the volume ratio of ethanol to water was 1:20, and the mixture was heated and stirred at 60 °C for 1 h. A 2 M hydrochloric acid solution was added to the mixture at a constant drip rate of 1 mL / min using a microinjection pump, and the mixture was heated and stirred at 60 °C for 1 h to obtain sol A.
[0041] S1.4: Add modified carbon fiber to sol A to prepare a mixed solution B containing 10 mg / L modified carbon fiber, and perform ultrasonic treatment at 60 °C for 30 min;
[0042] S1.5: 3 wt% of the composite lubricant and 1 wt% of polyethylene glycol were added to the mixed solution B, and stirred on a magnetic stirrer at a speed of 500 r / min for 1 h to obtain a gel precursor;
[0043] S1.6: Use a fully automatic spin coater to evenly coat the gel precursor on the surface of the metal substrate to be coated. The spin coating speed is 3000 r / min and the spin coating time is 2 min. Place the metal substrate coated with the gel precursor in a constant temperature drying oven and dry it at 100 °C for 2 h to obtain a dry gel film.
[0044] S1.7: Place the dry gel film in a tubular furnace and calcine it in an argon atmosphere at a temperature of 300°C for 1 h to obtain a coated substrate. After taking it out, use a grinder to polish the surface of the coated film. Then, immerse the coated film in ethanol and let it stand at room temperature for 30 min. After taking it out, dry it naturally to obtain the composite ceramic coating.
[0045] Wherein, the preparation method of modified carbon fiber is as follows:
[0046] S5.1: Soak 50 wt% carbon fiber in acetone for 30 min, wash it several times with deionized water and place it in deionized water, then add concentrated nitric acid solution at a flow rate of 0.5 mL / min, the mass fraction of the concentrated nitric acid solution is 70%, the addition time is 2.5 min, heat and stir at 70 °C for 1 h, and wash it with deionized water to obtain oxidized carbon fiber;
[0047] S5.2: The oxidized carbon fiber is placed in a microwave generator for irradiation. The setting parameters of the microwave generator are microwave power of 300 W, irradiation time of 30 min, irradiation temperature of 200 °C, and modified carbon fiber is obtained after natural cooling.
[0048] Wherein, the preparation method of the composite lubricant is as follows:
[0049] S6.1: MoS2 was placed in a ball mill for ball milling at a speed of 200 r / min for 1 h. Intermittent ball milling was used with a 1 min break after every 2 min of ball milling to obtain MoS2 powder with a particle size of 500 μm.
[0050] S6.2: Add 5 wt% molybdenum disulfide powder to the polytetrafluoroethylene emulsion and mix using a high-speed magnetic stirrer at a speed of 1000 r / min for 30 min to obtain a mixture C.
[0051] S6.3: Add 1 wt% titanate coupling agent to mixture C, heat and stir at 60 °C for 1 h to obtain a composite lubricant.
[0052] Example 2
[0053] In this embodiment, the tubular furnace uses a calcination temperature of 350°C.
[0054] S1.1: Use 500 mesh, 800 mesh and 1200 mesh water-abrasive sandpaper to polish the surface of the metal substrate step by step until it is bright, and use deionized water to clean the surface of the substrate;
[0055] S1.2: Place the polished metal substrate in an alkaline cleaning solution for 5 min, wash it with deionized water, and then place it in an acid cleaning solution for 5 min. Wash it with deionized water until the pH of the eluent is 7-8, and dry it at room temperature for 24 h to obtain the metal substrate to be coated;
[0056] S1.3: 85 wt% aluminum isopropoxide was dissolved in a mixture of ethanol and water, wherein the volume ratio of ethanol to water was 1:25, and the mixture was heated and stirred at 60 °C for 1 h. A 2 M hydrochloric acid solution was added to the mixture at a constant drip rate of 1 mL / min using a microinjection pump, and the mixture was heated and stirred at 60 °C for 1 h to obtain sol A.
[0057] S1.4: Add modified carbon fiber to sol A to prepare a mixed solution B containing 10 mg / L modified carbon fiber, and perform ultrasonic treatment at 60 °C for 30 min;
[0058] S1.5: 3 wt% of the composite lubricant and 1 wt% of polyethylene glycol were added to the mixed solution B, and stirred on a magnetic stirrer at a speed of 500 r / min for 1 h to obtain a gel precursor;
[0059] S1.6: Use a fully automatic spin coater to evenly coat the gel precursor on the surface of the metal substrate to be coated. The spin coating speed is 3000 r / min and the spin coating time is 2 min. Place the metal substrate coated with the gel precursor in a constant temperature drying oven and dry it at 100 °C for 2 h to obtain a dry gel film.
[0060] S1.7: Place the dry gel film in a tubular furnace and calcine it in an argon atmosphere at a temperature of 350°C for 1 h to obtain a coated substrate. After taking it out, use a grinder to polish the surface of the coated film. Then, immerse the coated film in ethanol and let it stand at room temperature for 30 min. After taking it out, dry it naturally to obtain the composite ceramic coating.
[0061] Wherein, the preparation method of modified carbon fiber is as follows:
[0062] S5.1: Soak 50 wt% carbon fiber in acetone for 30 min, wash it several times with deionized water and place it in deionized water, then add concentrated nitric acid solution at a flow rate of 0.5 mL / min, the mass fraction of the concentrated nitric acid solution is 70%, the addition time is 2.5 min, heat and stir at 70 °C for 1 h, and wash it with deionized water to obtain oxidized carbon fiber;
[0063] S5.2: The oxidized carbon fiber is placed in a microwave generator for irradiation. The setting parameters of the microwave generator are microwave power of 300 W, irradiation time of 30 min, irradiation temperature of 200 °C, and modified carbon fiber is obtained after natural cooling.
[0064] Wherein, the preparation method of the composite lubricant is as follows:
[0065] S6.1: MoS2 was placed in a ball mill for ball milling at a speed of 200 r / min for 1 h. Intermittent ball milling was used with a 1 min break after every 2 min of ball milling to obtain MoS2 powder with a particle size of 500 μm.
[0066] S6.2: Add 5 wt% molybdenum disulfide powder to the polytetrafluoroethylene emulsion and mix using a high-speed magnetic stirrer at a speed of 1000 r / min for 30 min to obtain a mixture C.
[0067] S6.3: Add 1 wt% titanate coupling agent to mixture C, heat and stir at 60 °C for 1 h to obtain a composite lubricant.
[0068] Example 3
[0069] In this embodiment, the tubular furnace uses a calcination temperature of 400°C.
[0070] S1.1: Use 500 mesh, 800 mesh and 1200 mesh water-abrasive sandpaper to polish the surface of the metal substrate step by step until it is bright, and use deionized water to clean the surface of the substrate;
[0071] S1.2: Place the polished metal substrate in an alkaline cleaning solution for 5 min, wash it with deionized water, and then place it in an acid cleaning solution for 5 min. Wash it with deionized water until the pH of the eluent is 7-8, and dry it at room temperature for 24 h to obtain the metal substrate to be coated;
[0072] S1.3: 85 wt% aluminum isopropoxide was dissolved in a mixture of ethanol and water, wherein the volume ratio of ethanol to water was 1:30, and the mixture was heated and stirred at 60 °C for 1 h. A 2 M hydrochloric acid solution was added to the mixture at a constant drip rate of 1 mL / min using a microinjection pump, and the mixture was heated and stirred at 60 °C for 1 h to obtain sol A.
[0073] S1.4: Add modified carbon fiber to sol A to prepare a mixed solution B containing 10 mg / L modified carbon fiber, and perform ultrasonic treatment at 60 °C for 30 min;
[0074] S1.5: 3 wt% of the composite lubricant and 1 wt% of polyethylene glycol were added to the mixed solution B, and stirred on a magnetic stirrer at a speed of 500 r / min for 1 h to obtain a gel precursor;
[0075] S1.6: Use a fully automatic spin coater to evenly coat the gel precursor on the surface of the metal substrate to be coated. The spin coating speed is 3000 r / min and the spin coating time is 2 min. Place the metal substrate coated with the gel precursor in a constant temperature drying oven and dry it at 100 °C for 2 h to obtain a dry gel film.
[0076] S1.7: Place the dry gel film in a tubular furnace and calcine it in an argon atmosphere at a temperature of 400°C for 1 h to obtain a coated substrate. After taking it out, use a grinder to polish the surface of the coated film. Then, immerse the coated film in ethanol and let it stand at room temperature for 30 min. After taking it out, dry it naturally to obtain the composite ceramic coating.
[0077] Wherein, the preparation method of modified carbon fiber is as follows:
[0078] S5.1: Soak 50 wt% carbon fiber in acetone for 30 min, wash it several times with deionized water and place it in deionized water, then add concentrated nitric acid solution at a flow rate of 0.5 mL / min, the mass fraction of the concentrated nitric acid solution is 70%, the addition time is 2.5 min, heat and stir at 70 °C for 1 h, and wash it with deionized water to obtain oxidized carbon fiber;
[0079] S5.2: The oxidized carbon fiber is placed in a microwave generator for irradiation. The setting parameters of the microwave generator are microwave power of 300 W, irradiation time of 30 min, irradiation temperature of 200 °C, and modified carbon fiber is obtained after natural cooling.
[0080] Wherein, the preparation method of the composite lubricant is as follows:
[0081] S6.1: MoS2 was placed in a ball mill for ball milling at a speed of 200 r / min for 1 h. Intermittent ball milling was used with a 1 min break after every 2 min of ball milling to obtain MoS2 powder with a particle size of 500 μm.
[0082] S6.2: Add 5 wt% molybdenum disulfide powder to the polytetrafluoroethylene emulsion and mix using a high-speed magnetic stirrer at a speed of 1000 r / min for 30 min to obtain a mixture C.
[0083] S6.3: Add 1 wt% titanate coupling agent to mixture C, heat and stir at 60 °C for 1 h to obtain a composite lubricant.
[0084] Comparative Example 1
[0085] In this comparative example, polytetrafluoroethylene is added to the gel precursor as a lubricant, and the remaining steps are consistent with the example.
[0086] Comparative Example 2
[0087] In this comparative example, molybdenum disulfide is added to the gel precursor as a lubricant, and the remaining steps are consistent with the example.
[0088] Comparative Example 3
[0089] In this comparative example, no composite / uncompounded lubricant is added to the gel precursor, and the remaining steps are consistent with the example.
[0090] Comparative Example 4
[0091] In this comparative example, unmodified carbon fiber is added to the gel precursor, and the remaining steps are consistent with the example.
[0092] Comparative Example 5
[0093] In this comparative example, no modified / unmodified carbon fiber is added to the gel precursor, and the remaining steps are consistent with the example.
[0094] Comparative Example 6
[0095] In this comparative example, modified / unmodified carbon fiber and composite / uncomposite lubricant are not added to the gel precursor, and the remaining steps are consistent with the embodiment.
[0096] The wear resistance of a self-lubricating composite ceramic coating prepared in the embodiment and the comparative example was tested in accordance with GB / T3810.7-2016.
[0097] The friction coefficient of a self-lubricating composite ceramic coating prepared in the embodiment and the comparative example was tested. The tribological properties of the samples were tested using a ball-on-disc high-temperature friction and wear testing machine. The sliding speed was 0.2 m / s, the load was 10 N, the wear track radius was 5 mm, the friction sliding time lasted 20 min, the test temperature was 37 °C, the friction torque was measured by a force sensor, and the friction coefficient was automatically calculated by a computer based on the applied external load.
[0098] A self-lubricating composite ceramic coating prepared in the embodiment and the comparative example was subjected to a toughness test. The toughness was measured by a single-sided straight-through notch beam method. A scriber was used to perform precise cutting in the film layer direction to form an incision with a width of 0.03 mm and a depth of 0.06 mm. A three-point bending test device was used to ensure that the sample was placed on two support points perpendicular to its long axis. A universal material testing machine was used to apply a constant load at a loading rate of 0.05 mm / min, and the fracture load and displacement data were recorded.
[0099] The experimental results are summarized in the following table:
[0100]
[0101] It can be seen from the experimental data that the various properties of the ceramic coating are optimal under the calcination condition of 300 ℃. After the calcination temperature is greater than 300 ℃, the self-lubricating performance decreases. This may be due to the instability of polytetrafluoroethylene in a high temperature environment. The present invention can achieve good results at a lower calcination temperature and has the advantages of environmental protection and energy saving. By comparing with the comparative data, it can be seen that the addition of modified carbon fiber makes the surface of the ceramic coating have better wear resistance and toughness; and the introduction of polytetrafluoroethylene in the lubricant significantly reduces the friction coefficient of the ceramic coating, and has better self-lubricating properties. The introduction of molybdenum disulfide further balances the self-lubricating and wear resistance of the ceramic coating.
[0102] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A process for preparing a self-lubricating composite ceramic coating, characterized in that: The specific process of preparing the self-lubricating composite ceramic coating is as follows: S1.1: Use 500 mesh, 800 mesh and 1200 mesh water-abrasive sandpaper to polish the surface of the metal substrate step by step until it is bright, and use deionized water to clean the surface of the substrate; S1.2: Place the polished metal substrate in an alkaline cleaning solution for 5 min, wash it with deionized water, and then place it in an acid cleaning solution for 5 min. Wash it with deionized water until the pH of the eluent is 7-8, and dry it at room temperature for 24 h to obtain the metal substrate to be coated; S1.3: 85 wt% aluminum isopropoxide was dissolved in a mixture of ethanol and water, heated and stirred at 60 °C for 1 h, hydrochloric acid solution was added to the mixture at a constant drip rate of 1 mL / min using a microinjection pump, and heated and stirred at 60 °C for 1 h to obtain sol A; S1.4: Add modified carbon fiber to sol A to prepare a mixed solution B containing 10 mg / L modified carbon fiber, and perform ultrasonic treatment at 60 °C for 30 min; The preparation method of the modified carbon fiber is as follows: S5.1: Soak 50 wt% carbon fiber in acetone for 30 min, wash it several times with deionized water and place it in deionized water, then add concentrated nitric acid solution at a flow rate of 0.5 mL / min, heat and stir at 70 °C for 1 h, and wash it with deionized water to obtain oxidized carbon fiber; S5.2: placing the oxidized carbon fiber in a microwave generator for irradiation, and obtaining modified carbon fiber after natural cooling; S1.5: 3 wt% of the composite lubricant and 1 wt% of the dispersant were added to the mixed solution B, and stirred on a magnetic stirrer at a speed of 500 r / min for 1 h to obtain a gel precursor; The preparation method of the composite lubricant is as follows: S6.1: MoS2 was placed in a ball mill for ball milling at a speed of 200 r / min for 1 h. Intermittent ball milling was used with a 1-min break after every 2 min of ball milling to obtain MoS2 powder with a particle size of 500 μm. S6.2: Add 5 wt% molybdenum disulfide powder to the polytetrafluoroethylene emulsion and mix them using a high-speed magnetic stirrer at a speed of 1000 r / min for 30 min to obtain a mixture C; S6.3: 1 wt% titanate coupling agent was added to mixture C, and the mixture was heated and stirred at 60 °C for 1 h to obtain a composite lubricant; S1.6: Use a fully automatic spin coater to evenly coat the gel precursor on the surface of the metal substrate to be coated. The spin coating speed is 3000 r / min and the spin coating time is 2 min. Place the metal substrate coated with the gel precursor in a constant temperature drying oven and dry it at 100°C for 2 h to obtain a dry gel film. S1.7: Place the dry gel film in a tubular furnace and calcine it in an argon atmosphere at a temperature of 300-400°C for 1 h to obtain a coated substrate. After taking it out, use a grinder to polish the surface of the coated film. Then, immerse the coated film in ethanol and let it stand at room temperature for 30 min. After taking it out, dry it naturally to obtain the composite ceramic coating.
2. The process for preparing a self-lubricating composite ceramic coating according to claim 1, characterized in that: The metal substrate in S1.1 is stainless steel.
3. The process for preparing a self-lubricating composite ceramic coating according to claim 1, characterized in that: The volume ratio of ethanol to water in S1.3 is 1:20-30.
4. The process for preparing a self-lubricating composite ceramic coating according to claim 1, characterized in that: The concentration of the hydrochloric acid solution in S1.3 is 2 M.
5. The process for preparing a self-lubricating composite ceramic coating according to claim 1, characterized in that: The dispersant in S1.5 is one of polyethylene glycol and polyvinyl alcohol.
6. The process for preparing a self-lubricating composite ceramic coating according to claim 1, characterized in that: The setting parameters of the microwave generator in S5.2 are as follows: microwave power is 300 W, irradiation time is 30 min, and irradiation temperature is 200°C.
